The effect of problem-based learning and project-based learning on the achievement motivation - Intan Kartika Sari (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
This study aimed to reveal: (1) the effect of PBL on the achievement motivation; (2) the effect of PjBL on the achievement motivation; and (3) differences of achievement motivation between the group taught using PBL and the group taught using PjBL. This study was a quasi experiment with the nonequivalent commparison group design. The population was grade V students of SD Negeri Lempuyangwangi in academic year 2016/2017. The data analysis used t-test and Univariate Analysis of Variance at the significant levelof 5%. The result are as follows: (1) PBL improved positively and significantly on theachievement motivation; (2) PjBL improved positively and significantly on theachievement motivation; and (3) there is a significant difference on theachievement motivation between the group taught using PBL and that taught using PjBL.